Lotka's Law and its Leimkuhler Representation - Rousseau, Ronald (Journal of Information and Knowledge, 1988)
We study the continuous form of Lotka's law. In particular, we are interested in the inflection point of the cumulative distribution when represented on semi-logarithmic scales (its so-called Leimkuhler representation). A comparison, with the discrete form shows that the results obtained for the continuous case are not accurate enough to give precise information on real data.